Suicidal shotgun wound on chest – An unusual entity - Kalra, Bhavya; Kumar Vashist, Yogesh; Malik, Yogendra; Chawla , Rahul; Garg , Anil; Sharma, Gaurav (Journal of Indian Academy of Forensic Medicine, 2019)
Injuries from firearms are on rise causing problem that severely affects the criminal justice and health-care systems of the country. Legal ownership of guns, male gender, and youth has been identified as risk factors for firearm injuries. Gunshot suicides committed with legally owned firearms, are occasionally encountered; rather people tend to use easier and cheaper methods like hanging or poisoning. The wounds in the suicidal cases due to firearms are generally in head region. We report a case in which the deceased a middle aged male individual who committed suicide using a licensed shotgun weapon, and had a wound over his chest.